Differences in Student Learning Outcomes Through the Application of Problem Based Learning (PBL) Learning Models With and Without Using Student Worksheets (LKPD) on Biodiversity Materials in Class X SMA S PAB 8 Saentis TP 2022/2023 - Panjaitan, Dina; Sidabutar, Hudson (ARKA INSTITUTE, 2023)
This study aims to determine the differences in student learning outcomes taught using the Problem Based Learning (PBL) learning model using LKPD and without LKPD on biodiversity material in class X SMA S PAB 8 Saentis. The type of research used is quasi experiment with Nonquivalent Control Group research design. The results showed that the average student learning outcomes in the Experiment class were 81.17 higher than in the Control class with a score of 75.92. Based on the results of the hypothesis test, a significance value was obtained on the posttest data, these results indicate that there are differences in the learning outcomes of students taught using the Problem Based Learning (PBL) learning model using LKPD and without LKPD on biodiversity material in class X SMA S PAB 8 Saentis TP 2022/2023.